An implantable composite scaffold for amplified chemodynamic therapy and tissue regeneration. Issue 14 (17th March 2023) - Chen, Jiafei; Wan, Shiqi; Fu, Yike; Zhou, Yi; Li, Xiang; Wang, Huiming
Abstract : An implantable hierarchical platform, based on BSO loaded tannic acid/Fe 3+ nanoparticles and VEGF loaded bioactive glass fibers, was constructed for simultaneous suppression of tumor growth and promotion of tissue repair. Abstract : Tissue regeneration and tumor cell killing after surgical resection are the two keys to achieving effective tumor therapy. In this study, an implantable system with combined functions of tumor therapy and tissue repair was constructed. Tannic acid (TA)/Fe 3+ nanoparticles with Fenton catalytic activity were loaded with GSH inhibitor BSO drug (BTF), and acted as the therapeutic factor to realize amplified chemodynamic tumor treatment. Bioactive glass (BG) fibers loaded with vascular endothelial growth factor (VEGF) were used as the drug carrier matrix with tissue repair function (BGV). Then the BGV@BTF composite fibers were obtained by anchoring BTF nanoparticles on the surface of BGV fibers. Under tumorous acidic conditions, BTF nanoparticles can be released from the composite fibers, and taken up by tumor cells. Facilitated by BSO with the GSH suppression effect and TA with Fe 3+ reducing properties, BTF nanoparticles can realize high oxidative stress in tumor cells and subsequent cell death. In addition, BG fibers and VEGF can both promote tissue regeneration and accelerate postoperative wound healing. The simultaneous suppression of tumor growth and promotion of tissue repair in this work is inspiring in the field of postoperative tumor treatment and recovery.